CMOS PHOTODIODE MODEL USING VHDL-AMS - Salahuddin, Nur Sultan (Majalah Ilmiah Matematika Komputer, 2007)
The objectives of this research is to designed and simulated CMOS photodiodes models usingVHOL-AMS with the AOVance-MS (AOMS) simulation tool of Mentor Graphics. The Photodiodemodels show a logarithmic response in illumination and are capable of detecting blue or green lightemitting diode. The result is fast and thorough design verification before the expense of fabrication.Key Words: light, diffusion, substrate, drift